Análise da fase oral da deglutição em indivíduos com doença pulmonar obstrutiva crônica - Tomasi, Lidia Lis (2018)
In addition to effects on quality of life of patients and functional ventilatory impairment, Chronic Obstructive Pulmonary Disease (COPD) produces changes in the swallowing function. The oral phase of swallowing is voluntary and corresponds to the act of positioning the bolus in the mouth and carrying out the posterior projection of it to the oropharynx. The analysis of the temporal quantitative variable oral transit time, including its definitions, markers of beginning and ending, swallowing of different consistencies and volumes of food are of extreme importance for the knowledge and regulation of the times in different populations and for the aid in the treatment and therapeutic management of swallowing dysfunctions. The aim of the present study was to analyze the oral phase of swallowing in individuals with COPD. This is a cross-sectional, descriptive and quantitative study involving patients with a medical and spirometric diagnosis of COPD, accompanied by the pulmonary rehabilitation program of the Hospital Universitário de Santa Maria, RS. The patients were submitted to Videofluoroscopy of deglutition (VFD) to quantitatively characterize the swallowing biomechanics, and the dental evaluation for oral health and dental condition analysis. The analysis of VFD exams was performed by three blinded judges who analyzed the variables oral transit time (OTT) and total oral transit time (TOTT), pre-swallow posterior spill, delayed initiation pharyngeal reflex and pharyngeal residue by means of software. The statistical tests were: Intraclass correlation coefficient, t test for equality of means, Wilcoxon test and Student t test. We studied 25 patients (15 men and 10 women), with a mean age of 65 years (41 to 77 years). It was observed OTT of 2.09s for liquid consistency and 1.61s for pasty, and TOTT of 2.34s and 1.84s for liquid and pasty consistencies, respectively. The OTTs are altered and larger as the severity of COPD increases. For both consistencies, the delayed initiation pharyngeal reflex occurred in higher anatomical regions. There was absence of pre-swallow posterior spill and pharyngeal residue in most patients. Most of the analyzed individuals had poor dental condition. It was concluded that there were alterations in the oral phase of swallowing of COPD subjects, with change in the quantitative variable OTT for the liquid and pasty consistencies